Study on the interaction of interfacial tension between water and oil surfaces in the presence of aluminium coated with polyvinylpyrrolidone (PVP) nanoparticles - Muhammad Faris, Raffizal; Mohd Zulkifli, Mohamad Noor; Mohd Shaiful Zaidi, Mat Desa; Irawan, Sonny; Wayo, Dennis Delali Kwesi (Universiti Malaysia Perlis (UniMAP), 2024)
Applications of nanotechnology are frequently used in the oil and gas sector. However, nanoparticles boost sand consolidation, lower interfacial tension between water and oil, and improve the mobility of trapped oil to increase crude oil recovery in enhanced petroleum recovery (EOR). Using aluminium PVP-coated low-porosity sand packing, the effects of nanoparticles on interfacial tension and water-oil surface contact were examined in this study. The horizontal column was filled with low-porosity sand, and the nanopowders were suspended in deionized water. The four distinct nanoparticle suspension pore volumes (PV) used in this experiment are 0.25, 0.5, 0.75, and 1.0 PV. At the column's output, the sample is then deposited, and the effluent is analysed and contrasted using IFT and viscosity with a solid viscometer. In this investigation, it was discovered that the water target zone had a very limited pore volume and only received 0.52 PV of injected nanoparticles. The better the oil can be extracted, the lower the viscosity and IFT value. The removal of the oil droplet and increased oil output for EOR could result from the transport of PVP nanoparticles coated with aluminium.